The Hubungan Pengetahuan, Sikap, dan Praktik (KAP) Masyarakat terhadap Pengelolaan Sampah Rumah Tangga Berbasis 3R - Tri Hapsari, Azkiya; Suherman Jaksa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Household waste is one of the major contributors to environmental problems. Waste management based on the 3Rs is an important strategy in reducing negative impacts on health and ecosystems. This study aims to review the literature on the relationship between knowledge, attitudes, and practices of the community in managing household waste based on the 3R principles. The method used was a literature study by collecting literature from Google Scholar and Science Direct. The results showed that good knowledge encourages positive attitudes and more effective waste management practices. Education, especially to housewives, is proven to increase awareness and active participation in sorting and processing waste. Successful waste management requires active community involvement, infrastructure support, and ongoing mentoring. In conclusion, the strong relationship between knowledge, attitude and practice shows the importance of an integrated approach to household waste management based on the 3R principles to create a clean, healthy and sustainable environment. The contribution of this research to science is through the review of various field studies from a number of regions in Indonesia, and emphasizes the urgency of community-based education, especially for strategic groups such as housewives. Educational efforts to increase active participation and awareness of the 3R principles can be used as a reference in designing intervention programs by both the government and non-governmental organizations.